Fire on the Water : Sailors, Slaves, and Insurrection in Early American Literature, 1789-1886 - Warren, Lenora (Book collections on Project MUSE., 2018)
"This book tells a new story about the troubled history of abolition and slave violence by examining representations of shipboard mutiny and insurrection in late eighteenth- and early nineteenth-century Anglo-American and American literature. The book centers on four black sailors, whose experiences with slavery and insurrection either inspired or found resonance within fiction. Through these sailors and their fictional avatars, Warren argues that a lost history of the politics of insurrection resurfaces. This history has been either largely ignored or subsumed under the generic political anxieties of the abolitionist movement and widespread fears of a large-scale slave revolt. These stories of sailors, both real and fictional, reveal how the history of mutiny and insurrection is both shaped by, and resistant to, the prevailing abolitionist rhetoric surrounding the efficacy of armed rebellion as a response to slavery. This book is a call to consider, or reconsider, how the confluence of politics, language, and narrative are complicit in shaping the ways in which we think about race and violence. Using the backdrop of the ocean to highlight both the expansive imaginary and the perilous reality of undoing oppressive hierarchies through mutiny, Fire On the Water challenges scholars to consider how violence gets categorized as "revolutionary" or "aberrant.""--